Influence of damping resistance in electromagnetic transients using alternate structures of p circuits - Santos, M. O. [UNESP]; Jus, L. H. [UNESP]; Prado, A. J. [UNESP]; Gennaro, Elmer Mateus; Filho, J. Pissolato (Institute of Electrical and Electronics Engineers (IEEE), 2017)
For modeling the transmission lines with lumped elements, it is necessary to use a large amount of p circuits in cascade. However, using this type of model, numerical simulations are affected by numerical errors that cause numerical oscillations. Thus, a damping resistor is inserted (RD) to dampen oscillations and reduce errors in simulations of electromagnetic transient phenomena propagation in transmission lines. For the analysis of the propagation of electromagnetic transient phenomena, transmission lines are decomposed into infinitesimal pieces modeled by p circuits. Currently, tests are performed with different p circuit structures. In this work, it is presented and discussed alternate structures where one type contains the resistance RD and the other does not contain RD. So, the cascade is composed by two types of p circuits for the representation of a transmission line. The mentioned numerical simulations are made by varying the amount of p circuits for analyzing the voltage at the line end. In this case, both structures of p circuits, with and without the damping resistance (RD) are applied alternately in the cascade that represents the analyzed transmission line. The obtained results are compared to those obtained with the application RD in every p circuit of the cascade. The application of alternate structures for the electromagnetic transient simulation was implemented in order to reduce the computational simulation time maintaining the accuracy obtained previously with the application of RD for whole p circuits of the model. Based on the obtained results, the alternate structures do not maintain the same accuracy of the application of RD for all p circuits, even increasing the number of these elements.